2018
DOI: 10.1152/jn.00130.2018
|View full text |Cite
|
Sign up to set email alerts
|

Error, rather than its probability, elicits specific electrocortical signatures: a combined EEG-immersive virtual reality study of action observation

Abstract: Detecting errors in one's own actions, and in the actions of others, is a crucial ability for adaptable and flexible behavior. Studies show that specific EEG signatures underpin the monitoring of observed erroneous actions (error-related negativity, error positivity, mid-frontal theta oscillations). However, the majority of studies on action observation used sequences of trials where erroneous actions were less frequent than correct actions. Therefore, it was not possible to disentangle whether the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(117 citation statements)
references
References 109 publications
5
109
3
Order By: Relevance
“…The interaction type (Complementary/Imitative) and the movement type (Precision/Power) factors were randomized trial-by-trial and pooled together. While an unequal number of Correction and No-Correction trials is usually used to emphasize the salience of one condition with respect to another we demonstrated that randomly selecting an equal number of trials for the two distributions does not change the results (Pezzetta et al, 2018).…”
Section: Experimental Taskmentioning
confidence: 69%
See 2 more Smart Citations
“…The interaction type (Complementary/Imitative) and the movement type (Precision/Power) factors were randomized trial-by-trial and pooled together. While an unequal number of Correction and No-Correction trials is usually used to emphasize the salience of one condition with respect to another we demonstrated that randomly selecting an equal number of trials for the two distributions does not change the results (Pezzetta et al, 2018).…”
Section: Experimental Taskmentioning
confidence: 69%
“…Although reported separately in the analysis, Theta and Alpha modulation shows a similar and correlated pattern (see Table 2). In previous error-related literature, Theta and Alpha have both been found over fronto-central electrodes during the processing of errors , Pezzetta et al, 2018. However, Trujillo and Allen (2007) have argued that activity in the lower Alpha band is due to leakage of the Theta frequency to the neighbouring bands.…”
Section: Error-related Responses In Time-frequency Domainmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, a source for the reduced feeling of ownership over the avatar limb may also be the fact that the participants' and the avatar's body never assumed a matched position. However, previous evidence reported illusory ownership even when participants were still and the virtual limb performed reach‐to‐grasp movement (Pavone et al, ; Pezzetta, Nicolardi, Tidoni, & Aglioti, ; Spinelli, Tieri, Pavone, & Aglioti, ). A possible explanation of this difference might rely on the number of trials, consistently greater in these previous experiments (i.e., a greater number of trials could increase the illusory sensation).…”
Section: Discussionmentioning
confidence: 93%
“…While changes in alpha and gamma were specific to the hemisphere from which feedback was provided, theta showed a bilateral pattern of modulation, being higher in the DOWN than the UP state in motor areas in both hemispheres. While mid-frontal theta activity has been linked to error monitoring 46 the role of lateralized theta activity close to the sensorimotor hotspot electrode and its symmetric counterpart is less clear. Slower rhythms exert effects over larger distances, and are thought to be involved in long-range communication 40 .…”
Section: Discussionmentioning
confidence: 99%